Hope : new philosophies for change - Zournazi, Mary (Pluto Press, 2002)
Mary Zournazi, in conversation with leading writers and philosophers from around the world, explores the connections between hope and our capacity to change our situation, to understand and overcome the new forms of fear and alienation in everyday life. Contributing their thoughts and visions to these fascinating conversations, Julia Kristeva, Ghassan Hage, Michel Serres, Alphonso Lingis, Brian Massumi, Christos Tsiolkas and many others provide personal and political accounts of hope, and innovative ways to consider identity, community and class experience.